Regional Operational Programs – an Opportunity for Development for Small and Medium Size Business Sector (Economic and Political Thought, 2013)
The article presents many different issues connected with the diverseattitude towards the programming periods, the assessment of state of theProgram assumptions and its implementation. Moreover, the use of the EuropeanUnion funds by Lower Silesian Voivodeship is thoroughly discussed.